2015
DOI: 10.4103/0975-9476.146546
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic activity of chickpea sprouts supplementation in ovariectomy-induced dyslipidemia in rats

Abstract: Background:Phytoestrogens are increasingly becoming popular as alternatives for hormone replacement therapy in postmenopausal condition.Objective:In this study, the antihyperlipidemic effect of chickpea (Cicer arientum) sprouts was evaluated in ovariectomy-induced dyslipidemia in rat model in comparison with standard antihyperlipidemic agent atorvastatin.Materials and Methods:A total of 24 female adult Wistar rats were divided into four groups that is, Group I - Control; Group II - Ovariectomized (OVX) rats; G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
2
5
0
1
Order By: Relevance
“…The dyslipidaemia after menopause is characterized by high levels of TC and LDL-cholesterol, followed by decreased HDL-cholesterol levels, what may accelerate atherosclerotic processes 39 . In the present study, high levels of TC and LDL-cholesterol were observed in the ovariectomized rats, in agreement with a previous report 44 . However, TAG levels were decreased in both OVX and OVX + GbE rats, probably due to estrogen deficiency.…”
Section: Discussionsupporting
confidence: 94%
“…The dyslipidaemia after menopause is characterized by high levels of TC and LDL-cholesterol, followed by decreased HDL-cholesterol levels, what may accelerate atherosclerotic processes 39 . In the present study, high levels of TC and LDL-cholesterol were observed in the ovariectomized rats, in agreement with a previous report 44 . However, TAG levels were decreased in both OVX and OVX + GbE rats, probably due to estrogen deficiency.…”
Section: Discussionsupporting
confidence: 94%
“…Remarkably, the oral administration of the higher dose of chickpea ‘Giza 1’ extract (CA500) significantly restored the levels of serum total cholesterol, LDL, HDL, and triglycerides to the standard group indicating hepatoprotective activity with preservation of cellular integrity and antilipidemic effect. These results complying with previous reports on chickpeas sprout ( Sharma, 1987 ; Harini et al, 2015 ) ( Table 2 ).…”
Section: Resultssupporting
confidence: 94%
“…Germinated chickpeas have antioxidant, antihypertensive, antihyperlipidemic, antiadipogenic, and antidiabetic properties. 4–6…”
Section: Introductionmentioning
confidence: 99%